Integrating Augmented Reality Technology in Magnetic Field Learning: A Systematic Literature Review - Haris, Venny; Alias, Siti Nursaila; Ayop, Shahrul Kadri (STKIP Singkawang, 2024)
The aim of this study was to uncover research trends in the use of augmented reality (AR) in magnetic field learning from 2012 to 2023. The review in this study followed the guidelines of Kitchenham, B. and Charters, which consisted of three stages: planning, conducting, and reporting the review. During the planning stages of the review, 107 articles were identified using keywords. The remaining articles were examined according to inclusion and exclusion criteria, so that 21 articles were further processed. A review stage is then carried out, followed by reporting of the review results. The results of this study suggest that the use of augmented reality (AR) to teach magnetic fields is primarily focused on teaching high school students. The aspects that have attracted the most attention when analyzing the implementation of AR in magnetic field education are learning/academic performance, perception and attitude. The most commonly used forms of AR in the study of magnetic fields are mobile applications, AR-based learning experiments, 3D simulations, and real-time simulations, all of which aim to explain abstract concepts and facilitate experimental explorations. Quantitative research design is the most commonly used approach in this field. The primary data collection tools used in this study include achievement tests, surveys, and questionnaires.